2021
DOI: 10.3389/fped.2021.634798
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset Sepsis in Neonates - A Population-Based Study in South-West Norway From 1996 to 2018

Abstract: Background: The epidemiology of early-onset sepsis (EOS) may change over time. Longitudinal surveillance of causative pathogens, antibiotic susceptibility patterns and antibiotic therapy is important for optimal therapy strategies.Objectives: To describe the incidence of culture-confirmed EOS, causative pathogens, antibiotic susceptibility patterns and antibiotic therapy over a 23-year period.Methods: Retrospective population-based study from a single-center neonatal intensive care unit at Stavanger University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…After implementing intrapartum antibiotic prophylaxis, the incidence and mortality of EOS have decreased significantly in the past decades, especially in developed countries [ 1 , 2 ]. The incidence of EOS was 0.32–0.97 per 1000 live births in Europe, comparable to reports from the USA (1.08/1000) and Australia (0.67/1000) [ 1 , 2 , 3 , 4 , 5 ]. However, its incidence remains higher in developing countries, where data is scarce [ 6 , 7 ].…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…After implementing intrapartum antibiotic prophylaxis, the incidence and mortality of EOS have decreased significantly in the past decades, especially in developed countries [ 1 , 2 ]. The incidence of EOS was 0.32–0.97 per 1000 live births in Europe, comparable to reports from the USA (1.08/1000) and Australia (0.67/1000) [ 1 , 2 , 3 , 4 , 5 ]. However, its incidence remains higher in developing countries, where data is scarce [ 6 , 7 ].…”
Section: Introductionsupporting
confidence: 79%
“…The etiology of EOS has changed dramatically after implementing guidelines for routine group B Streptococcus (GBS) screening. Although it has been shown that E. coli has become the most frequently detected pathogen in EOS of extremely preterm infants, the leading microorganism for EOS is still GBS in developed countries [ 4 , 8 ]. Evidence indicates that the pathogen distribution of EOS differs among developing and middle-income countries in the Middle East region and Asia, where GBS is less frequently reported, while Gram-negative pathogens, such as Klebsiella pneumoniae and E. coli , are the major pathogens and are less likely to be susceptible to currently recommended empirical antibiotic therapy [ 6 , 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“… 32–35 Comparably, a study from Norway reported EOS incidence of 0.97/1000 live births between 1996–2018. 36 Whereas, a study in Greece reported a weighted EOS incidence rate of 1.8/1000 live births, 37 indicating some variability in the HIC data. A higher EOS was similarly reported in a large study among preterm infants conducted in China (upper-middle income) between 2015–2018 (n=27,532 enrolled infants) with an incidence of 9.7/1000 live births.…”
Section: Epidemiology Of Neonatal Sepsis In Lmics: a Summarymentioning
confidence: 99%
“…Streptococcus agalactiae (also termed as group B Streptococcus , GBS) is a leading cause of invasive disease in neonatal and young infant patients, although intrapartum antimicrobial prophylaxis (IAP) has significantly reduced the incidence of early onset GBS infection ( Tan et al, 2021 ; Vatne et al, 2021 ; Wong et al, 2021 ). A recent survey revealed that families with a baby with GBS infection suffered significant financial and psychological difficulties ( Raybould et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%